EFFECTIVENESS OF THE YOUTH, SPORTS, AND TOURISM OFFICE IN EMPOWERING YOUTH ORGANIZATIONS IN BALANGAN REGENCY - Fakhri Fakhri; Rina Emilyana; Junaidi Junaidi (PT. Antis International Publisher, 2025)
Objective: This study aims to evaluate the effectiveness of the Youth, Sports, and Tourism Office in empowering youth organizations in Balangan Regency, and to identify the factors influencing this empowerment. Method: A qualitative research approach was employed, utilizing descriptive-qualitative techniques. Data were gathered through interviews, observation, and documentation, with a purposive sampling method selecting 10 participants. The analysis involved data reduction, presentation, and drawing conclusions, ensuring credibility through member checks and persistent observation. Results: The findings indicated that while the organizational structure of youth organizations in Balangan Regency is clear, there are issues with resource allocation, inadequate leadership, and poor cooperation between youth organizations and the local government. The annual youth development budget was deemed insufficient, and youth organizations faced difficulties in implementing strategic programs due to a lack of coordination and limited resources. Novelty: This research highlights the gap between the government’s policies for youth empowerment and the practical challenges faced by youth organizations, offering insights into the need for improved resource management, cooperation, and leadership to enhance the effectiveness of youth empowerment programs.